Designing an Inclusive and Sustainable Halal Tourism Industry Model - Eva Zunia Khoiriyah; Firdaus Diaz (ASEAN Journal of Halal Study, 2025)
The halal tourism industry is growing rapidly along with the increasing number of global Muslim travelers and awareness of sharia-based consumption. Indonesia as a country with the largest Muslim population has great potential in this sector, but still faces challenges such as low halal literacy, inadequate infrastructure, and weak collaboration between stakeholders. This research aims to develop a conceptual model for the development of the halal tourism industry through a literature study of Scopus indexed scientific articles for the period 2020-2025. The method used is a descriptive qualitative study with a thematic analysis approach to 10 selected articles. The results showed that an effective halal tourism development strategy includes four main pillars: policy and regulation, human resource development, technological innovation and digital marketing, and preservation of cultural and environmental values. In conclusion, the conceptual model offered can be used as a basis for the formulation of national and local policies and strategies in building inclusive and sustainable halal tourism destinations.